2018
DOI: 10.1016/j.enconman.2018.06.083
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the ionic liquid-microwave assisted one-step biodiesel production process from wet microalgal biomass

Abstract: This study illustrates the influence of ionic liquid (IL)-microwave heating on the direct transesterification (in-situ transesterification) of wet Nannochloropsis sp. biomass to biodiesel. The ionic liquid used was 1-ethyl-3-me-thylimmidazolium methyl sulphate [EMIM][MeSO4]. Direct transesterification process variables such as the wet algae to methanol ratio, reaction time and methanol to IL ratio influencing the biodiesel production were optimised using response surface methodology (RSM). The results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…The ruptured microalgae cell releases all its intracellular contents and these contents are freely available to be extracted using ILs. Recent work conducted by Wahidin et al [85] reported that by using 1-ethyl-3-methylimmidazolium methyl sulfate as extractive solvent and combined with microwave heating, it is possible to convert directly Nannochloropsis sp. biomass to biodiesel in a single step in situ transesterification process.…”
Section: Microwave-assisted Ionic Liquid Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ruptured microalgae cell releases all its intracellular contents and these contents are freely available to be extracted using ILs. Recent work conducted by Wahidin et al [85] reported that by using 1-ethyl-3-methylimmidazolium methyl sulfate as extractive solvent and combined with microwave heating, it is possible to convert directly Nannochloropsis sp. biomass to biodiesel in a single step in situ transesterification process.…”
Section: Microwave-assisted Ionic Liquid Extractionmentioning
confidence: 99%
“…biomass to biodiesel in a single step in situ transesterification process. The approach has achieved efficient biodiesel production per unit of microalgae biomass [85].…”
Section: Microwave-assisted Ionic Liquid Extractionmentioning
confidence: 99%
“…The use of ionic liquid 1‐ethyl‐3‐methylimmidazolium methylsulfate has enabled to produce biodiesel from wet algae by direct trans‐esterification in methanol under microwave heating . The synergetic effect of combining IL – methanol solvent and microwave heating produced biodiesel in 42 % yield based on dry biomass weight . The direct conversion of wet oleaginous yeast biomass to fatty acid biodiesel using 1‐ethyl‐3‐methylimidazoliumethylsulfate and KOH is also known .…”
Section: Biodiesel Synthesis Using Ionic Liquidsmentioning
confidence: 99%
“…[200] The synergetic effect of combining IL -methanol solvent and microwave heating produced biodiesel in 42 % yield based on dry biomass weight. [200] The direct conversion of wet oleaginous yeast biomass to fatty acid biodiesel using 1-ethyl-3-methylimidazoliumethylsulfate and KOH is also known. [201] Some of the more recent (after 2012) applications of ILs in biodiesel synthesis are shown in Table 5.…”
Section: Biodiesel Synthesis Using Ionic Liquidsmentioning
confidence: 99%
“…Moreover, ILs have excellent microwave absorbance because of their ionic character. Therefore, they are able to transfer energy rapidly via ionic conduction under microwave fields [25,26].…”
Section: Introductionmentioning
confidence: 99%